KOMPOSISI MEDIA TANAMAN DALAM MENINGKATKAN VIABILITAS BENIH YLANG-YLANG (Canangium odoratum forma genuina) - Erma Suryani; Herwita Idris (Fapetrik-UMPAR, 2022)
Aquilaria malaccensis Lam. is a gaharu-producing plant with excellent quality and high social, cultural, and economic values. Ylang-ylang plants (Canangium odoratum forma genuina) in Indonesia are forma Guinena familia Annonaceae which have many benefits. One of the benefits is as a producer of essential oils produced from the distillation of flowers. Ylang-ylang plants can be propagated generative and vegetative, but currently, many are done in a generative way. For this reason, a study was carried out to know the composition of plant media in increasing the viability of ylang-ylang (Canangium odoratum forma genuina) seeds. The study was arranged experimentally using a factorial design based on a completely randomized design in a greenhouse. The first factor was the planting medium consisting of andosol soil, andosol soil + citronella ash, ultisol + manure, and sawdust planting medium. While the second factor was the size of the seeds, namely seeds from large, medium, and small fruit, each treatment combination was repeated three times. Parameters observed were fruit weight for each characteristic, dry weight of 50 seeds/seed, germination power, growth speed, and vegetative growth of seeds (seed height, number of leaves, leaf length, leaf width, number of roots, root length, and biomass). The research results were that the weight of large fruit was 3.016 – 4.749 g, with a significant seed weight of 0.054 – 0.056g, the best germination in andosol medium large fruit 57.78% early germination on the 40th day after sowing. The vegetative growth is a seed height of 6.60 cm, the average number of leaves is 6.05 leaves, the length of the leaves is 5.41 cm, and the width is 1.94 cm. A number of roots is 7.00 pieces, with root length of 13.50 cm with 17.62 g biomass.